PERBEDAAN TINGKAT KELELAHAN KERJA BERDASARKAN KEBIASAAN SARAPAN PADA PEKERJA KURIR PENGIRIMAN BARANG JNE DI KOTA MEDAN TAHUN 2015 - Muhammad bayu akbar; kalsum *; eka lestari mahyuni (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT Breakfast in the morning is an important activity before physical activities  that  beneficial to prevent energy deficiency that causes fatigue. The high  demand  of delivery of goods inversely to the workers who were not significant that caused fatigue  in work. The purpose of this study was to see the difference in fatigue levels based on the breakfast habit JNE courier workers in the city of Medan in 2015. Analytic research methods survey with a cross-sectional design. The population in this study was the couriers who work in the morning shift from 7:00 to 16:00 o'clock with a total sample of 75couriers using total sampling method. Fatigue was measured  using a questionnaire fatigue in scale subjectively Industrial Fatigue Research Committee (IFRC) and categorized  into levels of low, medium, high, and very high. The results showed that the courier workers who do the breakfast at most levels of fatigue is at  low level are 27 people (96.4%) and workers who do not have breakfast  at medium  levels are 39 people (83%). Mann-Whitney test results showed p = 0.0001 <0.05 means that there are differences in levels of fatigue based on the breakfast habit JNE courier workers in the city of Medan in 2015. Suggested to the couriers do not skip breakfast and get a breakfast in preventing fatigue and to support the work carried out for more leverage.